(untitled) (Italian Review of Legal History, 2024)
On May 12, 1898 the first military engagement of the Spanish-American War in Puerto Rico took place with a naval battle between the United States Navy under the command of Admiral William T. Sampson and the capital city of San Juan. During the bombardment US ships destroyed military buildings and civilian infrastructure including a hospital, an orphanage, and a church, also resulting in 18 wounded and 5 civilian deaths. Even though it is suggested by the historiographic literature of the Spanish-American War (1898) that the bombardment of San Juan was an illegal act of war by the United States, there is a need for a legal-historical analysis to that effect, including all the available primary sources from published resources, and also, documentation found in historical archives, together with the international law of the period to comprehend this affirmation better. Henceforth, this critical analysis of the historical facts and the international law of the period can elucidate the bombardment of San Juan as a historical case in which the law of war often omits justice when bombing against civilians.